Perencanaan Strategis Sistem Informasi Pada Sistem Informasi Bisnis Menggunakan Ward and Peppard Pada Mister Pithik - Titan Kurniawan; Frederik Samuel Papilaya (Journal of Information Technology Ampera, 2022)
Mister Pithik is a small and medium business engaged in the food business in the form of rice bowls which is quite well known in Salatiga and Ambarawa. Currently, Mister Pithik has experienced many developments in his business, but in his business processes, Mister Pithik has not implemented systems and information technology as a whole and is still applying manual methods in the work process, such as recording sales, cashiers, and bookkeeping, so the work process is not effective. and frequent errors in processing business data. Therefore, it is necessary to have the right IS/IT strategic planning to meet the business needs of Mister Pithik to support existing business processes to be more effective and efficient. This research was conducted using the Ward and Peppard method which consists of several stages of analysis, namely Value Chain analysis, SWOT analysis, PEST analysis, and internal and external analysis from Mister Pithik. The results of this study are strategic recommendations from the results of the analysis of the internal and external business environment which are compiled and mapped using the McFarlan Strategic Grid, accompanied by gap analysis and implementation plans for the next few years.